Withholding-tax non-compliance: the case of cum-ex stock-market transactions - Thiess Buettner; Carolin Holzmann; Felix Kreidl; Hendrik Scholz (International Tax and Public Finance, 2020)
This paper explores withholding-tax non-compliance in the context of dividend taxation. It focuses on a specific type of stock-market transactions around ex-dividend dates, so-called “cum-ex” trades, which caused considerable revenue losses due to illegitimate tax refunds in Germany and other countries. We use a stylized model of the stock-market equilibrium to analyze the incentives of traders on the German stock market and find that cum-ex trades are only profitable for both buyer and seller in the presence of collusive tax fraud. Our empirical analysis of market data for publicly traded German stocks from 2009 to 2015 confirms that transaction numbers of stocks suitable for cum-ex trades show the expected increase shortly before ex-dividend dates in the period before the tax refunding was reformed. In line with the collusion hypothesis, effects on stock-market prices are not found.
Keywords: H26; G12; 340; Tax compliance; Tax evasion; Withholding taxes; Collusion; Tax fraud; Tax refunding; Cum-ex trades; Ex-dividend date; Dividend taxes; Capital gains taxes